2019
DOI: 10.1007/s12325-019-0895-1
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Effectiveness of Ipragliflozin for Type 2 Diabetes in Japan: 12-Month Interim Results of the STELLA-LONG TERM Post-Marketing Surveillance Study

Abstract: IntroductionThe present interim report of the STELLA-LONG TERM study aimed to examine the safety and effectiveness of ipragliflozin in real-word clinical practice in Japan using data up to 12 months. We also evaluated the effect of ipragliflozin on aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in patients with normal vs. abnormal liver function.MethodsThis is an ongoing 3-year post-marketing surveillance study. We analyzed data from Japanese type 2 diabetes mellitus (T2DM) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
14
1
2
Order By: Relevance
“…The safety and efficacy of ipragliflozin in type 2 diabetes patients has been shown through clinical trials and post‐marketing surveys. Several studies have shown that ipragliflozin lowers blood glucose levels in an insulin‐independent fashion, and hence is expected to be efficacious in type 1 diabetes, as well as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of ipragliflozin in type 2 diabetes patients has been shown through clinical trials and post‐marketing surveys. Several studies have shown that ipragliflozin lowers blood glucose levels in an insulin‐independent fashion, and hence is expected to be efficacious in type 1 diabetes, as well as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the approval of the first SGLT2 inhibitor in Japan in 2014, the class has become widely used. In several post-marketing surveillance (PMS) studies, including in elderly patients, adverse drug reactions (ADRs) occurred at similar or lower frequencies to clinical trials, with no new safety concerns [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The STELLA-LONG TERM study is an ongoing post-marketing surveillance study examining the safety and effectiveness of ipragliflozin in real-world clinical practice in Japan. Several analyses based on interim cutoff data and various subgroup analyses have been conducted so far [12][13][14][15][16] . One of the published subgroup analyses evaluated the safety and effectiveness of ipragliflozin in non-elderly vs elderly patients (<65 vs !65 years) using data from 3, 12 and 24 months.…”
Section: Introductionmentioning
confidence: 99%